A missional hermeneutic for the transformation of theological education in Africa - Niemandt, Nelus (HTS teologiese studies, 2019)
The wide acceptance and maturation of the theology of missio Dei is the most important development in the theology of mission in recent times. It introduced a radically new understanding of mission and theology, and flowing from that a re-appropriation of ecclesiology. Mission studies are also characterised by a new appreciation of mission from the margins: liberation theology and the associated discourses on decoloniality, deep engagement in contextuality and the explosion of missional ecclesiology (missional church). This apostolic orientation of the church is of the utmost importance in the reflection on the future of theology. This research attends to the postcolonial discourse as an important critique of colonialism and understands the emancipation of Africanised or decolonised theological education as an inevitable and positive development. Contextual sensitivity, attention to diverse power structures and a predisposition to appreciate diversity open imaginative possibilities for theological education. This leads to the argument that decolonial African theology must confront issues of biblical hermeneutics. The proposal of this research is that missional hermeneutic is an excellent starting point. It describes the contours of a missional hermeneutic, attending to mission as central to the Biblical story, the meaning of mission and the conviction that reading Scriptures constitutes an essential part of missional praxis. Missional hermeneutic is a centring vision and purpose for theological education. The argument is for a missional curriculum that defines a centre that unifies the various disciplines, one that places mission and missiology at the heart of theological education.